2019
DOI: 10.1002/da.22893
|View full text |Cite
|
Sign up to set email alerts
|

Symptom profiles of late‐life anxiety and depression: The influence of migration, religion and loneliness

Abstract: Objective To examine (1) clinically relevant anxiety with comorbid depression in an older population, and the presentation of subthreshold symptoms; (2) to assess anxiety and levels of comorbid depression associated with migration, religion, loneliness and long‐term illness. Methods Analysis of Wave 1 of The Irish Longitudinal Study on Ageing (TILDA) (2009‐2011). Latent class analysis (LCA) was used to define indicative diagnoses of anxiety and depression. We then assessed associations between sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
2
13
2
3
Order By: Relevance
“…Those who reported poorer mental health also showed greater risk, consistent with other evidence on loneliness and mental health in general [ 47 ] as well as risk of loneliness during the pandemic specifically [ 15 , 18 , 47 ]; indeed, we noted a four-fold increased risk of severe loneliness during the pandemic. As others have suggested, the relationships and pathways between poor mental health and loneliness are often connected, with many shared and socially excluding factors linked to both conditions, e.g., stigma, anxiety, low self-esteem and motivation [ 30 ]. As with other studies [ 15 , 21 ], we found that people most likely to report loneliness are those who also considered themselves financially insecure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who reported poorer mental health also showed greater risk, consistent with other evidence on loneliness and mental health in general [ 47 ] as well as risk of loneliness during the pandemic specifically [ 15 , 18 , 47 ]; indeed, we noted a four-fold increased risk of severe loneliness during the pandemic. As others have suggested, the relationships and pathways between poor mental health and loneliness are often connected, with many shared and socially excluding factors linked to both conditions, e.g., stigma, anxiety, low self-esteem and motivation [ 30 ]. As with other studies [ 15 , 21 ], we found that people most likely to report loneliness are those who also considered themselves financially insecure.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness was assessed by the modified 5-item UCLA loneliness scale, which has been validated in previous studies [27][28][29][30][31][32]. This included items relating to how often respondents feel "lonely" and "in tune with" the people around them (reverse scored) in addition to the 3 items in the short UCLA scale [33].…”
Section: Loneliness: Pre-covid-19 and During Covid-19 Pandemicmentioning
confidence: 99%
“…According to the recent reports, depression and anxiety are considered as the major psychiatric disorders around the world particularly in the Western region. 29 , 30 It is well known that both of the disorders affect the daily life of the human beings. At present number of drugs are available in the markets for depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of their study on university students, Diehl et al found that social loneliness increased the levels of depression and anxiety. Curran et al reported that social loneliness and having fewer close ties are significant characteristics of the lives of those who have comorbid anxiety and depression/subthreshold depression. In Beutel et al's study, it was found that loneliness plays a role in health problems such as depression, anxiety, and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%